2016
DOI: 10.12973/eurasia.2017.00611a
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Promote Anxiety toward Math on High School Students

Abstract: Regardless of the social or economic status of a student, it is a fact that math is always present. This discipline is considered as a competitive tool for achieving a more productive life. However, the gap in academic achievement is big. Consequently, in the last decades the research on education has set attention on this point. Therefore, this research aims to prove that there is anxiety toward math on high school students at a private institution Rioverde in San Luis Potosí, México and find if there is a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 4 publications
1
2
0
1
Order By: Relevance
“…The findings of the study revealed the following factors as the causes of mathematics anxiety among students; teachers' bad attitude, not having enough time to solve mathematics questions, having too many students in a class, not getting help when solving Mathematics homework and the abstract nature of the mathematics as a course. This finding supports the work of Puteh (2002); Mohamed & Tarmizi (2010) and Escalera-Chávez et al, (2016) who found that, if students perceived "mathematics as difficult" in their formative years there is likelihood for mathematics anxiety to be triggered. Also, the study support that of Kargar, Ahmad & Bayatc (2010) and Parvathamma & Sharanamma, (2010) who discovered a negative correlation between anxiety, attitude and self-confidence respectively.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…The findings of the study revealed the following factors as the causes of mathematics anxiety among students; teachers' bad attitude, not having enough time to solve mathematics questions, having too many students in a class, not getting help when solving Mathematics homework and the abstract nature of the mathematics as a course. This finding supports the work of Puteh (2002); Mohamed & Tarmizi (2010) and Escalera-Chávez et al, (2016) who found that, if students perceived "mathematics as difficult" in their formative years there is likelihood for mathematics anxiety to be triggered. Also, the study support that of Kargar, Ahmad & Bayatc (2010) and Parvathamma & Sharanamma, (2010) who discovered a negative correlation between anxiety, attitude and self-confidence respectively.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…Históricamente, una de las mayores dificultades que ha existido a lo largo del proceso educativo en las instituciones ha sido el aprendizaje de las matemáticas, siendo la falta de motivación, ansiedades, creencias e incluso la utilización inapropiada de métodos en la etapa inicial de la educación las causas más frecuentes para que esto suceda (Díaz, García, y Pacheco, 2016;Rojas-Kramer et al, 2017). El aprendizaje de las matemáticas depende de la actitud del estudiante y su percepción hacia la materia.…”
Section: Motivación En El Aprendizaje De Las Matemáticas En Modalidad...unclassified
“…Nervousness and discomfort caused by mathematics in high school students occur when students lack self-confidence [3]. Since anxiety in mathematics is often posed inside mathematical problems [1], it is an obstacle that students must resolve because it affects their mathematics achievement [4].…”
Section: Introductionmentioning
confidence: 99%